2005
DOI: 10.1111/j.1745-4514.2005.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Natto Bacillus Contains a Large Amount of Water-Soluble Vitamin K (Menaquinone-7)

Abstract: Bacillus natto ( Bacillus subtilis natto ) was cultivated, and an analysis was conducted after performing lysozyme treatment and water extraction of the culture supernatant and the B. subtilis natto cells. The intracellular existence of a large amount of water-soluble vitamin K (Menaquinone-7: MK-7) was established. The existence of small amounts of other types of vitamin K2 including MK-4 and PK was also confirmed in the culture solution (watersoluble fractions). The amount of water-soluble menaquinone-7 in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…Epidemiological and animal studies have demonstrated a high relationship between consumption of natto products and low incidence of cardiovascular diseases (Iwai, Nakaya, Kawasaki, & Matsue, 2002;Park, Kang, Kim, & Yeo, 2012) and osteoporosis (Ikeda et al, 2006). To date, these health benefits were generally considered to be due to the production of nattokinase, antioxidative peptides, vitamin K2, and the formation of aglyconic isoflavones by microbial glucosidase during processing (Samaranayaka & Li-Chan, 2011;Wei, Chen, & Chen, 2008;Yanagisawa & Sumi, 2005). With this study, besides these known constituents, natto may contribute its biological functions via G7P, demonstrated to improve the oral absorption of genistein.…”
Section: Discussionmentioning
confidence: 80%
“…Epidemiological and animal studies have demonstrated a high relationship between consumption of natto products and low incidence of cardiovascular diseases (Iwai, Nakaya, Kawasaki, & Matsue, 2002;Park, Kang, Kim, & Yeo, 2012) and osteoporosis (Ikeda et al, 2006). To date, these health benefits were generally considered to be due to the production of nattokinase, antioxidative peptides, vitamin K2, and the formation of aglyconic isoflavones by microbial glucosidase during processing (Samaranayaka & Li-Chan, 2011;Wei, Chen, & Chen, 2008;Yanagisawa & Sumi, 2005). With this study, besides these known constituents, natto may contribute its biological functions via G7P, demonstrated to improve the oral absorption of genistein.…”
Section: Discussionmentioning
confidence: 80%
“…The concentration of vitamin K 2 increases to 124 times that in the soybeans at the start of the fermentation by natto bacteria [76]. Vitamin K 2 stimulates the formation of bone.…”
Section: Nattomentioning
confidence: 99%
“…A Wbrinolytic enzyme, designated nattokinase [69], not only breaks up blood clots (thrombi) but also breaks down built-up Wbrin that has been associated with heart disease [10,68]. No other enzyme came close to nattokinase in studies of 173 diVerent foods that were examined for their potential thrombolytic activities [76]. Dipicolinic acid, found in natto, has anti-bacterial activity against E. coli O157 and against Helicobacter pylori [53,70], the causative agent of stomach ulcers.…”
Section: Nattomentioning
confidence: 99%
“…It has been unique to historical countries in different parts of the world, e.g. milk fermentation "yoghurt" in Bulgaria [1], vegetable fermentation "suan cai" in China [2], "kimchi" in Korea [3], "natto" and "mizo" in Japan [4,5], Gundruk, Sinki, and khalpi in India [6]. In Thailand there are famous traditional fermented products called "Nham" and "Miang".…”
Section: Introductionmentioning
confidence: 99%